#### Answer

$f^{-1}(-3)=-2$

#### Work Step by Step

RECALL:
(1) If $(a, b)$ is on the graph of $f(x)$, then $f(a) = b$.
(2) If $f(a)=b$, then $f^{-1}(b)=a$
The given graph contains $(-2, -3)$
This means that $f(-2) = -3$.
Thus, $f^{-1}(-3)=-2$.

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$f^{-1}(-3)=-2$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.